2017
DOI: 10.1111/jvh.12836
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐free therapy is associated with restoration of type I IFN response in HIV‐1 patients with acute HCV infection who achieve SVR

Abstract: Interferon (IFN)-free direct-acting antiviral agents (DAAs) have revolutionized chronic hepatitis C virus (HCV) treatment; early studies suggest excellent efficacy in acute HCV. However, changes in innate immune responses during DAA therapy for acute HCV are unknown. We studied interferon-stimulated gene (ISG) expression and related cytokines/chemokines in HIV-infected patients with acute HCV receiving sofosbuvir plus ribavirin (SOF+RBV) as part of the A5327 clinical trial. ISG expression was determined from P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Rapid HCV clearance following DAA therapy has been shown to restore innate antiviral responses in both peripheral blood and liver, 27 particularly type 1 interferon responses and natural killer cell responses. 28,29 Restoration of innate immunity following DAA treatment may impact upon HBsAg seroclearance and may explain the dynamic changes observed in our HBV/HCVcoinfected patients. 30 miR-122 and miR-125b are important host factors in both HBV and HCV lifecycles.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid HCV clearance following DAA therapy has been shown to restore innate antiviral responses in both peripheral blood and liver, 27 particularly type 1 interferon responses and natural killer cell responses. 28,29 Restoration of innate immunity following DAA treatment may impact upon HBsAg seroclearance and may explain the dynamic changes observed in our HBV/HCVcoinfected patients. 30 miR-122 and miR-125b are important host factors in both HBV and HCV lifecycles.…”
Section: Discussionmentioning
confidence: 99%
“…DAA therapy also rapidly restored the activated type I IFN response in PBMCs, assessed in terms of the ISG expression level and STAT1 phosphorylation [102,108,109]. A recent study from our group demonstrated that pre-treatment ISG activation in PBMCs might be due to type I IFN activation of JAK-STAT signaling [108].…”
Section: Impact Of Daa Treatment On Types I and Iii Ifn Responses To mentioning
confidence: 68%
“…In another study, among patients with HIV-1 that had acute HCV infections, ISGs were downregulated in PBMCs during DAA therapy. After therapy, the ISG levels increased in patients that relapsed, but not in patients that achieved a SVR [109]. In patients with HCV infections, baseline ISG levels in PBMCs were affected by the IFNL4 genotype [98].…”
Section: Impact Of Daa Treatment On Types I and Iii Ifn Responses To mentioning
confidence: 95%
“…Restoration of immunologic responses after HCV clearance with interferon-free treatment has also been reported [ 12 14 ]. Hepatitis B reactivation during or after interferon-free treatment for HCV may be associated with the restoration of adaptive and innate immune responses [ 12 14 , 18 , 19 ]. Thus, interferon-free treatment for HCV may have an effect on hepatic immunity and activity of autoimmune liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Immune restoration in the liver is occasionally associated with HCV infection [ 10 , 11 ]. Studies using interferon-free regimens demonstrated an immune restoration of immunologic responses after HCV clearance [ 12 14 ]. Thus, HCV clearance has effects on the human immunologic response.…”
Section: Introductionmentioning
confidence: 99%